The comparison between authentic and graded material in order to keep reading motivation of basic intensive english students, semester l-2016, Bachelor in English Language Teaching, Foreign language Department, University of El Salvador - Espinoza Salgado, Ana Priscila; Marroquín Gómez, Izamar Rosmery; Serrano Cruz, Isis Vanessa (2024)
The following research project focused on the comparison between authentic and graded material in order to keep reading motivation of Basic Intensive English students, Semester I- 2016, Bachelor in English Teaching Language, Foreign Language Department, at University of El Salvador. With this study, the researchers analyzed which material was better for students in order to start reading from now on since the reading habit is really important as they will become English teachers.